Fault Tree Analysis of chemical cargo contamination by using fuzzy approach. Issue 12 (15th July 2015) - Senol, Yunus Emre; Aydogdu, Yusuf Volkan; Sahin, Bekir; Kilic, Ibrahim
Highlights Chemicals are the toughest cargoes carried by ships. Probabilities of root causes and their contributions to top event are determined. Comparing to the actual case, the result is observed as parallel to the real case. This study could lead to make cost-benefit analysis and risk management strategy.